Understanding the crystal structures, dielectric and optical properties of Sr2CaTeO6, SrLaLiTeO6, SrLa1-xNdxLiTeO6 and SrLaLiTe1-xMnxO6 double perovskites / Muhammad Zharfan Mohd. Halizan - Mohd. Halizan, Muhammad Zharfan (2022)
The research carried out for this thesis has concentrated on double perovskite materials Sr2CaTeO6, SrLaLiTeO6, SrLa1-xNdxLiTeO6 (x=0.25, 0.50, 0.75) and SrLaLiTe1-xMnxO6 (x=0.02, 0.04, 0.06, 0.08, 0.10) have been successfully prepared through conventional solid-state procedures. The single–phase monoclinic P21/n structure was determined from structural study for both Sr2CaTeO6 and SrLaLiTeO6 compounds. The morphological study exhibited an increase of grain sizes when the dopant is added until the maximum grain sizes achieved at concentrations of x=0.50 and x=0.08 in Nd– and Mn–doped SrLaLiTeO6, respectively.